PAIN MANAGEMENT IN HOSPITALIZED CANCER PATIENTS: SYSTEMATIC REVIEW - Giovani, Calista; Monica Carissa, Theodora; Priska Adelin, Claudia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Cancer pain affects a significant percentage of patients globally, impacting their quality of life. Despite available guidelines, undertreatment remains a concern, with barriers to effective pain management, highlighting the need for a systematic review. This review aims to assess current practices, identify barriers, evaluate intervention effectiveness, explore patient experiences, and investigate adherence to guidelines, providing comprehensive insights for optimizing pain management in hospitalized cancer patients. Methods: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result Our search produced 16 results. After looking at the titles and summaries, we found several papers that fit our criteria. At first, we excluded few articles because they were written in review and case report style. But after reading the full papers carefully, we included five papers in our final analysis. These papers included cross-sectional, retrospective chart review study, retrospective analysis of pancreatic cancer patients receiving CPN for pain, a multicenter, prospective, longitudinal study of inpatients with cancer pain who received SPC, and blinded, randomized, sham-controlled pilot cross-over trial. Conclusion: Our systematic review on pain management in hospitalized cancer patients highlights the correlation between pain documentation adequacy, opioid prescriptions, and the need for targeted palliative care education. Additionally, insights from interventions such as CT-guided CPN, SPC, and TENS underscore their potential benefits, calling for further exploration within the systematic review's overarching aim of understanding effective pain management strategies for hospitalized cancer patients.